Anatomy of a microearthquake sequence on an active normal fault - Stabile, T. A. (Nature Publishing Group, 2012)
The analysis of similar earthquakes, such as events in a seismic sequence, is an effective tool with which to monitor and study source processes and to understand the mechanical and dynamic states of active fault systems. We are observing seismicity that is primarily concentrated in very limited regions along the 1980 Irpinia earthquake fault zone in Southern Italy, which is a complex system characterised by extensional stress regime. These zones of weakness produce repeated earthquakes and swarm-like microearthquake sequences, which are concentrated in a few specific zones of the fault system. In this study, we focused on a sequence that occurred along the main fault segment of the 1980 Irpinia earthquake to understand its characteristics and its relation to the loading-unloading mechanisms of the fault system.